OsHAC4 is critical for arsenate tolerance and regulates arsenic accumulation in rice - Xu, Jiming; Shi, Shulin; Wang, Lei; Tang, Zhong; Lv, Tingting; Zhu, Xinlu; Ding, Xiaomeng; Wang, Yifeng; Zhao, Fang‐Jie; Wu, Zhongchang (The New phytologist, 2017)
Soil contamination with arsenic (As) can cause phytotoxicity and elevated As accumulation in rice grain. Here, we used a forward genetics approach to investigate the mechanism of arsenate (As(V)) tolerance and accumulation in rice. A rice mutant hypersensitive to As(V), but not to As(III), was isolated. Genomic resequencing and complementation tests were used to identify the causal gene. The function of the gene, its expression pattern and subcellular localization were characterized. OsHAC4 is the causal gene for the As(V)-hypersensitive phenotype. The gene encodes a rhodanase-like protein that shows As(V) reductase activity when expressed in Escherichia coli. OsHAC4 was highly expressed in roots and was induced by As(V). In OsHAC4pro-GUS transgenic plants, the gene was expressed exclusively in the root epidermis and exodermis. OsHAC4-eGFP was localized in the cytoplasm and the nucleus. Mutation in OsHAC4 resulted in decreased As(V) reduction in roots, decreased As(III) efflux to the external medium and markedly increased As accumulation in rice shoots. Overexpression of OsHAC4 increased As (V) tolerance and decreased As accumulation in rice plants. OsHAC4 is an As(V) reductase that is critical for As(V) detoxification and for the control of As accumulation in rice. As(V) reduction, followed by As(III) efflux, is an important mechanism of As(V) detoxification.